Gestión financiera y su efecto en la rentabilidad de la empresa de recolección de desechos consorcio ingenio Urdaneta, año 2022. - Angamarca Montalván , Josselin Denisse (2024)
Financial management worldwide is constantly changing, with competitiveness predominating in the current market, through financial planning that affects the increase in the general value of the company and therefore its profitability. Currently in Ecuador, organizations tend to have the need to make changes oriented towards higher quality financial models, in such a way that the importance is implemented in facets such as administration and accounting, where the economic structure must be profitable. The objective in carrying out this thesis work is to evaluate the effect of Financial Management on the Profitability of the waste collection company Consorcio Ingenio Urdaneta, year 2022. Within the applied research methodology, the analytical method was used, deductive and inductive, finally the population and research sample were detailed, as well as the research techniques and instruments that were used for the preparation, collection, processing and analysis of the information. Among the results that the methods used yielded, we have that the analyzes allowed us to know the weak points of the financial statements; in the qualitative analysis, the lack of knowledge on the part of the management about financial management, the use of profitability and liquidity indicators, was determined. And an improvement plan was established to be implemented to improve the profitability and decision making of the solid waste collection company Consorcio Ingenio Urdaneta.